Frequent respiratory pathogens of respiratory tract infections in children attending daycare centers - Bonfim, Caroline M. [UNESP]; Nogueira, Mauricio L.; Simas, Paulo Vitor M. [UNESP]; Gardinassi, Luis Gustavo A. [UNESP]; Durigon, Edison L.; Rahal, Paula [UNESP]; Souza, Fátima Pereira de [UNESP] (Sociedade Brasileira de Pediatria, 2011)
Objectives: To identify and characterize respiratory viruses that infect children from daycare centers with symptoms of respiratory infection and to evaluate the association of clinical and epidemiological disease data with the identified virus.Methods: We conducted a study between 2003 and 2005 in 176 children with respiratory infection symptoms attending a municipal daycare center. Samples from nasopharyngeal secretion were tested by reverse transcriptase polymerase chain reaction and positive samples for picornavirus were sequenced.Results: All 782 collected samples were analyzed and 31.8% were positive for at least one of the studied respiratory viruses. Respiratory infections were characterized by the presence of mild symptoms of the upper respiratory tract, the most common of which were runny nose and cough. In the 2 years of study, most cases of infection occurred in autumn and winter, but respiratory viruses were detected throughout all the study period.Conclusions: Respiratory viruses and respiratory infections caused by them are part of the daily life of children attending daycare centers. Our results show the great impact that respiratory infections have on these children and suggest that more attention must be paid to viral pathogens.